SKRINING DAN IDENTIFIKASI ISOLAT BAKTERI ENDOFIT UNTUK MENGENDALIKAN PENYAKIT HAWAR DAUN BAKTERI PADA BAWANG MERAH - Zurai Resti; Trimurti Habazar; Deddi Prima Putra; . Nasrun (Universitas Lampung, 2013)
Screening and identification of endophytic bacteria to control bacterial leaf blight disease on Shallot. The experiment was conducted in Laboratory and Green House, from January to June 2012. Laboratory experiment consisted of three steps: (1) isolation of endophytic bacteria from healthy onion roots, (2)In planta /screening of endophytic isolates capable of reducing bacterial leaf blight disease, and (3) molecular identification of potential endophytic isolates. Treatments of in planta test were arranged in Completely Randomized Design. Collected isolates were tested for their capability in controlling bacterial leaf blight disease on shallot. The variables observed were disease incidence, disease severity, and shallot yield. The results showed that out of 82 isolates successfully isolated, 56 isolates (68.29%) were Gram positive, and 26 isolate (31.71%) were Gram negative. All isolates were HR negative and pathogenicity negative. Six endophytic isolates showed better performance in inducing resistance and increasing onion yield. Based on 16S rRNA sequence the six isolates were Bacillus cereus strain P14 , Bacillus cereus strain Se07, Bacillus sp H1, Bacillus sp SJ1 and Serratia marcescens strain PPM4.